Comparative Study of Tangible Tabletop and Computer-Based Training Interfaces for Cognitive Rehabilitation - Song, Kyuye; Lee, Sekwang; Pyun, Sung-Bom; Kim, Laehyun (UNIVERSAL ACCESS IN HUMAN-COMPUTER INTERACTION: USERS AND CONTEXT DIVERSITY, PT III, 2016)
Computer-based training (CBT) has lately been applied for the cognitive rehabilitation of stroke patients. However, most CBT programs do not consider body movement, which is important for cognitive rehabilitation because body movement (action) and thought (mind) are deeply correlated. Based on the coupling of action and mind, we propose a tangible tabletop-based training (TTBT) platform, E-CORE. We conducted a comparative study between E-CORE (TTBT) and RehaCom (CBT), for which we recruited eight patients as participants. We used the performance score yielded by the Intrinsic Motivation Inventory (IMI), the System Usability Scale (SUS), and the Questionnaire for User Interaction Satisfaction (QUIS) for quantitative analysis, and observation and semi-structured interviews as tools for qualitative analysis. Even though the user group was comparatively small, we found that E-CORE (TTBT) increases patients' motivation for rehabilitation.